Ecological footprint of Rawalpindi; Pakistan's first footprint analysis from urbanization perspective. (1st January 2018) - Rashid, Audil; Irum, Ayesha; Malik, Ikram Ali; Ashraf, Aniqa; Rongqiong, Liu; Liu, Guijian; Ullah, Habib; Ali, Muhammad Ubaid; Yousaf, Balal
Abstract: Estimates of footprint have rationalized the approach of environmental input-output assessments. In this study, the Ecological Footprint denotes the bioproductive area needed to sustain a population. We evaluated the living style standards of urbanized areas of Rawalpindi (i.e. Bahria Town and Gulraiz Colony) to calculate their Ecological Footprint. Comprehensive information was obtained from the population of these two areas by questionnaires and subsequent analysis using the Ecological Footprint calculator formulated by Redefined Progress. The Ecological Footprint of Bahria Town is 8.6 g ha (global hectares) and Gulraiz Colony is 6.9 g ha, which indicates that the urban population in these two areas are living a luxurious life style and consuming resources far more than the biocapacity of Pakistan. Another aspect that emerged from this study is that the biocapacity of Pakistan is unable to meet the needs of people due to population increase. Both Bahria Town and Gulraiz Colony have Ecological Footprints higher than national standard values, which illustrates that if all others lived like people in the studied areas then Pakistan's Ecological Footprints (4.7 g ha) would double and overpopulation will have further stress on the ecosystem. We propose maximum utilization of green resources and adaption of energy saving habits as immediate intervention measures to reduce the Ecological Footprint. Graphical abstract: Image 1 Highlights: Urban population is competing for Pakistan's declining biocapacity. Luxury and high per capita consumption are directly linked in newly developed urban areas. Ecological Footprint of Bahria Town and Gulraiz Colony are 8.68 and 6.99 g ha respectively. Carbon Footprint of these two urban areas is two times higher than national values.